Social Media Metadata Forensic Ontology Model - Tuharea, Ibnu Rohan; Luthfi, Ahmad; Ramadani, Erika (Mobile and Forensics, 2023)
The escalating use of compact electronic gadgets like smartphones and smartwatches, along with social media platforms, has led to a new dimension of criminal activities. Advancements in digital forensics, which investigates digital evidence, have become noteworthy. Researchers David Christopher Harrill and Richard P. Mislan devised Small-Scale Digital Device Forensics (SSDDF) for examining miniature digital devices used in criminal undertakings. Edlira Kalemi and Sule Yildirim-Yayilgan demonstrated the application of ontology in social media forensics, deciphering Android system frameworks related to social media data extraction. However, their investigations mainly focused on social media, overlooking the role of gadgets used by criminals and victims. Extracting digital data from these devices remains pivotal for securing relevant evidence from social media. Notwithstanding, incorporating SSDDF and understanding Android system structures have significantly contributed to digital forensic methodologies. These enhancements can bolster the investigation process, capturing and analyzing critical digital evidence from compact electronic appliances and social media platforms. The advent of SSDDF and elucidating Android system structures have offered invaluable inputs to digital forensics, enhancing efficacy in amassing significant evidence from small electronic devices and social media platforms.